Walsh, Daphne. New Perlican Photograph of two women on either side of a man. - Barrett, Terra (1945)
A photograph of Alma (Warren) Coates (left), Pete Warren (middle), and Leah (Warren) Hobbs (right) in 1945, New Perlican. Above the photograph it says "Family Memories." The photograph was printed by Kodak.